PEMBELAJARAN JOYFULL LEARNING DENGAN PUZZLE GAME BERBASIS EKSPERIMEN: MENINGKATKAN MINAT BELAJAR SISWA MATA PELAJARAN IPA - Praharsini, Adiba; Ahsani, Eva Luthfi (Prodi PGMI STIT Sunan Giri Bima, 2023)
This study aims to describe the implementation of Joyful Leaning learning with Experiment-based Puzzle Games in increasing student learning interest in Class IV Science at MI Muhammadiyah 2 Kudus accompanied by various factors that support and hinder it. This research is included in the descriptive qualitative research where the type of research is field research. Data will be obtained through interviews, observation and documentation of research subjects, namely teachers and students at MI Muhammadiyah 2 Kudus. The validity of the data obtained will be tested by testing the validity of the data in the form of extending observations, increasing persistence and member checks. The data analysis that will be carried out uses Miles and Huberman's theory. The results of this study indicate that the application of Experiment-based Joyful Learning with Puzzle Games in class IV Science subjects at MI Muhammadiyah 2 Kudus begins with preliminary activities, core activities and closing activities. Joyful Learning Learning with Experiment-based Puzzle Game was able to increase students' interest in learning, namely at the 1st meeting with results (55%: Fairly Good), 2nd meeting with results (60%: Fairly Good), 3rd meeting with results ( 64% : Good), and the 4th meeting with results (66% : Good). The supporting factors for Joyful Learning with experimental-based Puzzle Games are teachers and students, while the inhibiting factors are facilities and infrastructure as well as observational tools and materials. Factors supporting interest in learning for grade IV students in Science Subjects, namely teachers, students, student conditions, class conditions and the inhibiting factors are the lack of parental assistance and appreciation given by outstanding students as well as item numbers 9 and 14 indicators of interest in learning.